Application of the cranked Nilsson model in some light nuclei : The super backbend in 11B and 11C? - Ragnarsson, I.; Åberg, S.; Hakansson, H. B.; Sheline, R. K. (Nuclear Physics, Section A, 1981)
The Nilsson model of high-spin states is developed to include particle-hole excitations for rotation around an arbitrary axis. Potential-energy surfaces are calculated with constraints not only on the total spin but also on parity and signature. The method is applied to very light nuclei with A ~ 10. Good agreement for the ground-state bands of 8Be and 12C is obtained and predictions are made for the excitation energy of higher-spin states (I {greater-than or approximate} 4) of positive and negative parity. It is pointed out how the "positive-parity yrast levels" of 11B and 11C form a rotational band with a very small rotational parameter. When taken in conjunction with the much larger rotational constants of the negative-parity bands, this can be interpreted in terms of a super backbend. We discuss the possible association of these positive-parity bands with a calculated potential-energy minimum at a large prolate deformation which for positive parity develops already at low spins. Special attention is paid to the question of signature splitting.